PERAN TEKNOLOGI TEPAT GUNA DALAM PENINGKATAN PRODUKTIVITAS DAN KEBERLANJUTAN USAHA BAGI KELOMPOK UMK KERIPIK TUMBASO DI PROBOLINGGO - Hendra, Joni; Supraptiningsih, Linda Kurnia; Hakim, Lukman; Avrylina, Nayla; gholi, Muhammad Al (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
The problem that is often experienced by production partners is that the process of frying chips still uses conventional methods, namely using a frying pan in general, so that in terms of quality it is constrained by production capacity, and in terms of quality the production results contain too much oil which causes bananas to become soft easily, apart from that. The use of appropriate technology in the form of a frying machine (Vacuum Frying) and an oil draining machine (Spinner) is a solution as an effort to increase efficiency and productivity as well as sustainable business at Tuimbaso MSEs in Lambangkuning village, Lumbang district, Probolinggo. PkM activities aim to increase the efficiency and sustainability of the chips business. The strategy used is apart from designing and making frying machine technology, it also provides training and assistance in marketing management and financial management, so that it is hoped that partners will be able to improve human resources and have a positive impact related to improving business performance in a sustainable manner in and supporting the economy, especially local wisdom. The results or influences felt by partners in this program include partners being able to innovate or develop their production results through product diversification, and being able to expand the market through marker places such as Shopee, Tokopedia and so on. Keywords; TTG; Produktivity; Innovation; Sustainabilty; Business